Peran Produk Inovatif Cibay dalam Peningkatan Daya Saing UMKM Pawon Bu Tina di Kelurahan Kutisari - Wardani, Anisa Setyo; Swasti, Ika Korika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Improving the competitiveness of SMEs is crucial in the era of global competition. One strategy that can be used is to develop innovative products. This research aims to determine the role of cibay innovative products in improving the competitiveness of Pawon Bu Tina SMEs in the Kutisari Village. The research method uses a qualitative approach with a case study. Data was collected through in-depth interviews, observations, and documentation. The results show that cibay innovative products have successfully improved the competitiveness of Pawon Bu Tina SMEs. This is indicated by an increase in sales, customer satisfaction, and business image. The increase in cibay sales is due to a better taste, more affordable prices, and more attractive packaging design. The increase in customer satisfaction is due to innovative and attractive products, as well as good service. The improvement in the business image is due to recognition from the government and mass media, as well as customer trust. Therefore, cibay innovative products are an effective strategy for improving the competitiveness of SMEs.